Propolis extract promotes translocation of glucose transporter 4 and glucose uptake through both PI3K‐ and AMPK‐dependent pathways in skeletal muscle. (28th January 2013) - Ueda, Manabu; Hayashibara, Kaori; Ashida, Hitoshi
Abstract : It is well known that propolis has the ability to prevent hyperglycemia. However, the underlying mechanism is not yet fully understood. We therefore investigated whether a Brazilian propolis ethanol extract affects glucose uptake and translocation of insulin‐sensitive glucose transporter (GLUT) 4 in skeletal muscle cells. In L6 myotubes, the extract at 1 μg/mL significantly promoted GLUT4 translocation and glucose uptake activity. Regarding the mechanism of GLUT4 translocation, propolis extract induced both PI3K and AMPK phosphorylation in a dose‐dependent manner in L6 myotubes. However, we could not define which pathway was preferentially associated with GLUT4 translocation, because both PI3K and AMPK inhibitors revealed off‐target effects to each other. The main polyphenols found in the propolis extract, artepillin C, coumaric acid, and kaempferide, promoted GLUT4 translocation in L6 myotubes. Additionally, these compounds activated both PI3K‐ and AMPK‐dependent dual‐signaling pathways. However, only kaempferide increased glucose uptake activity under our experimental conditions. Single oral administrations of propolis extract, at 250 mg/kg body weight, lowered postprandial blood glucose levels in ICR mice. The extract promoted GLUT4 translocation in skeletal muscle of rats and mice, but did not inhibit α‐glucosidase activity in the small intestine under our experimental conditions. It was confirmed that propolis extract promoted phosphorylation of both PI3K and AMPK in rat skeletal muscle. In conclusion, we show that Brazilian propolis has the potential to prevent hyperglycemia through the promotion of GLUT4 translocation in skeletal muscle and that kaempferide is one of the candidates for active compound in propolis. © 2013 BioFactors, 39(4):457–466, 2013